The role of credit unions in financial intermediation and development in the Bahamas - Deveaux, Shirl ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Examines the operations of credit unions as non-bank financial intermediaries in The Bahamas, investigating the nature and scope of these operations vis-à-vis the banking system. Comments on the regulatory environment in which these institutions operate. Examines whether Bahamian credit unions contribute in any way to development in the theoretical sense.